Negotiated Procedure Without Prior Publication: Red Flag for Limited Competition or for the Need to Increase Administrative Capacity and Control - Pavlova, Miglena (Research Papers, 2024)
New social reality in the European Union after the Covid-19 pandemic and the upheavals in world peace is shaped and determined to a large extent by the implementation of the European Recovery and Resilience Mechanism – the EU’s plan to support economic recovery and build a greener, more digital and a more sustainable post-crisis future. In the focus of this ambitious program of the Union also falls the reform of public procurement, as a determining factor of the business environment. In the National Recovery and Resilience Plan of the Republic of Bulgaria, goals related to the reduction of the number of negotiation procedures without prior publication have been set, but in the last year the level of the indicator has been increasing. Present research focuses on the use of the procedures of negotiation without prior publication, and the main research thesis is that the reason for this growth in Bulgaria is the incorrect application of the public procurement legislation and lack of effective ex-post control.